UMP and MTNP seal collaboration in Ulul Albab Certification Programme - Mimi Rabita, Abdul Wahit (2020)
Pekan, 19 August 2020 - Students from the tahfiz stream do not have to worry about continuing their studies at Universiti Malaysia Pahang (UMP) as they can also continue the Quran memorisation throughout their studies.